High intelligibility text-to-speech synthesis for Polish - J. IMIOŁCZYK; I. NOWAK; G. DEMENKO (Archives of Acoustics, 2014)
The paper presents the system of automatic synthesis of the Polish speech signal from text, developed over the last three years at the Department of Acoustic Phonetics in Poznań. The element generating the acoustic signal is a special-purpose IC controlled from a PC AT by means of original software comprizing the modules for text editing, phonemic transcription and synthesis of digital parameters. The speech signal, produced in real time, is highly intelligible, which opens up before the system a prospect of concrete applications in man–man and machine–man communication.